Impact of Artificial Intelligence on Academic Literacy among University Students in Indonesia: A Case Study - A Fadel Muhammad; Nur Astiana Hidayat Ardi; Nitswat, Nurhaliza; Sri Hardianti Nur; Razak, Annisa Zhalila; Fatjri Nur Tajuddin; Anzar Aquil; Moch. Nur Syahrus Syahbana (Scidac Plus, 2025)
The rapid adoption of Artificial Intelligence (AI) tools in higher education has transformed learning practices, prompting concerns about their influence on students’ critical thinking, originality, and independent engagement with academic materials. This study explores the perceived impact of AI on academic literacy among Indonesian university students, with particular attention to critical thinking, originality, and independent learning. Employing a qualitative approach, the study captures students' experiences and perspectives, revealing that while AI tools such as ChatGPT and Grammarly are perceived to enhance learning efficiency, they may also diminish deeper engagement with academic content and critical thinking processes. Many participants reported a tendency to rely on AI-generated summaries, which they associated with reduced independent analysis and creativity. Nevertheless, the findings suggest that when AI tools are integrated with thoughtful pedagogical strategies, they can support the development of academic literacy within ethical boundaries. The study underscores the importance of implementing AI literacy programs and ethical guidelines to foster responsible and reflective use of AI in academic contexts.